A Comparison of Two Models Predicting the Presence of Chronic Exertional Compartment Syndrome - Vignaud, Emeline; Menu, Pierre; Eude, Yannick; Maugars, Yves; Dauty, Marc; Fouasson-Chailloux, Alban (International Journal of Sports Medicine, 2021)
Clinical history and physical examination are usually not sufficient to diagnose leg chronic exertional compartment syndrome (CECS). Two predictive clinical models have been proposed. The first model by De Bruijn et al. is displayed as a nomogram that predicts the probability of CECS according to a risk score. The second model by Fouasson-Chailloux et al. combines two signs (post-effort muscle hardness on palpation or hernia). To evaluate those models, we performed a prospective study on patients who were referred for possible CECS. 201 patients underwent intra-compartmental pressure at 1-min post-exercise (CECS if ≥ 30 mmHg) – 115 had CECS. For the De Bruijn et al. model, the risk score was 7.5±2.2 in the CECS group and 4.6±1.7 in the non-CECS group (p<0.001) with an area under the ROC curve of 0.85. The model accuracy was 80% with a sensitivity of 82% and a specificity of 78%. Concerning Fouasson-Chailloux et al. model, the accuracy was 86%; the sensitivity and the specificity were 75 and 98%, respectively. The De Bruijn et al. model was a good collective model but less efficient in individual application. In patients having both muscle hardness and hernia, we could clinically make the diagnosis of CECS.
Keywords: chronic exertional compartment syndrome; leg; prediction; muscle hernia; muscle hardness